2019
DOI: 10.1007/s00253-019-10213-6
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about the influence of vacuum on bacterial biocenosis used in environmental biotechnologies?

Abstract: The article aims to show the increased interest in the applications of vacuum in the area of environmental biotechnology and the lack of research related to the effects of vacuum on bacteria and microbial communities. Information on the impact of vacuum on bacteria is limited and often comes from unrelated research fields. In most cases (astrobiology research, food preservation technologies), the exposure of microorganisms in vacuum is permanent for the whole life of a cell. In environmental science applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Indeed, only a few batch studies have discussed the impact of vacuum on microbes (Gnida, 2020;Kral et al, 2011;Rajhi et al, 2016;Verseux, 2020), and thus long-term impacts are largely unexplored. Kral et al (2011) investigated the impact of vacuum on different methanogens cultivated on Mars soil simulant and reported that methanogens survived for 10 days under 400 mbar at 35 °C but displayed minimal activity when vacuum pressure reached 50 mbar, indicating that lower pressure exerted more significant stress on methanogens.…”
Section: Vacuum Evaporation and Distillation Technologiesmentioning
confidence: 99%
“…Indeed, only a few batch studies have discussed the impact of vacuum on microbes (Gnida, 2020;Kral et al, 2011;Rajhi et al, 2016;Verseux, 2020), and thus long-term impacts are largely unexplored. Kral et al (2011) investigated the impact of vacuum on different methanogens cultivated on Mars soil simulant and reported that methanogens survived for 10 days under 400 mbar at 35 °C but displayed minimal activity when vacuum pressure reached 50 mbar, indicating that lower pressure exerted more significant stress on methanogens.…”
Section: Vacuum Evaporation and Distillation Technologiesmentioning
confidence: 99%
“…The current lowest pressure recorded for microbial growth is 0.7 kPa (7 mbar; Schuerger and Nicholson 2016 ). Nevertheless, low-pressure vacuum is used in biotechnologies, including biomining (Gnida 2020 ), and a bioreactor using low-pressure Mars-similar gas composition was successfully developed for cyanobacterial growth (Verseux et al 2021 ). This suggests that, with the appropriate adaptation and engineering, challenges posed by extraterrestrial atmospheric composition and pressure could be overcome not to limit biomining applications.…”
Section: Space Biomining Principlesmentioning
confidence: 99%
“…While the slightly acidic pH of 5.0 -6.0 is ideal for the hydrolytic microorganisms, the neutral pH and mesophilic conditions (30 -45 °C), optimized at 37 °C, in which the methanogenic species thrive, are ideal for them [13]. Moreover, vacuum impregnation's main mechanism is to displace gas in porous material with aqueous mixture by pressure [14], and the vacuum condition, that is empty of gas (completely anaerobic), can enhance the activity of the hydrolytic microorganisms, leading to better biomass hydrolysis [15]. Therefore, improved biomass hydrolysis can be achieved through ensiling under a vacuum at an ambient temperature of 26 -30 °C.…”
Section: Introductionmentioning
confidence: 99%